2022
DOI: 10.15766/mep_2374-8265.11275
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Justice: A Case-Based, Interactive Curriculum

Abstract: Introduction Reproductive injustices such as forced sterilization, preventable maternal morbidity and mortality, restricted access to family planning services, and policy-driven environmental violence undermine reproductive autonomy and health outcomes, with disproportionate impact on historically marginalized communities. However, curricula focused on reproductive justice (RJ) are lacking in medical education. Methods We designed a novel, interactive, case-based RJ cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…3 Additionally, Loder et al 4 have identified several components critical to any RJ curriculum: iours in clinical spaces and potential future behaviours. 6 We believe that the added value of the transformative learning theory-informed approach presented here is in its use of self-examination and critical assessment of assumptions. Use of these tools powerfully supports the teaching of element ( 7) of Loder's framework, in addition to generalizable skills in person-centred reproductive health for any patient-facing individual in a range of health professions (medicine, nursing, ancillary health services and beyond).…”
Section: How Should We Teach Reproductive Justice?mentioning
confidence: 91%
See 1 more Smart Citation
“…3 Additionally, Loder et al 4 have identified several components critical to any RJ curriculum: iours in clinical spaces and potential future behaviours. 6 We believe that the added value of the transformative learning theory-informed approach presented here is in its use of self-examination and critical assessment of assumptions. Use of these tools powerfully supports the teaching of element ( 7) of Loder's framework, in addition to generalizable skills in person-centred reproductive health for any patient-facing individual in a range of health professions (medicine, nursing, ancillary health services and beyond).…”
Section: How Should We Teach Reproductive Justice?mentioning
confidence: 91%
“…Existing published curricula on RJ use individual‐level passive learning methods such as watching videos along with self‐reflection questions 5 and case‐based learning paired with a group discussion about historical and present injustices, previously observed behaviours in clinical spaces and potential future behaviours 6 . We believe that the added value of the transformative learning theory‐informed approach presented here is in its use of self‐examination and critical assessment of assumptions.…”
Section: How Should We Teach Reproductive Justice?mentioning
confidence: 95%
“…An analysis of educational interventions revealed three main categories, namely one-time interventions (n = 10), workshops (n = 20), and semester courses (n = 6) (see Table 2). Regarding one-time activities, most interventions (n = 7) concentrated on enhancing the SH of the LGBTQ population [38,39,41,45,48,55,59]. However, there was no information available on the speci c principles of SHA models that were included in the intervention curricula.…”
Section: Intervention Typesmentioning
confidence: 99%
“…Most one-time educational intervention programs (n = 5) lasted two hours and utilized various teaching methods [32,41,45,48,59]. However, three studies did not report on the duration of educational interventions [31,38,55].…”
Section: Duration Of Educational Interventionmentioning
confidence: 99%
“…Reproductive justice concepts are being integrated into medical education, 23 and at least one published curriculum has included immigration barriers in the context of reproductive rights. 24 Yet, gaps remain in applying the reproductive justice framework to noncitizens and understanding the history of immigration law as a structural determinant of reproductive health for immigrants. Some of the most egregious examples of reproductive control arise within the U.S. immigration detention system, which restricts reproductive autonomy of immigrants on multiple fronts.…”
Section: Call To Actionmentioning
confidence: 99%